The role of electrophoretic deposition method in the creation of a biocomposit based on hydroxyapatite layers and silver nanoparticles; Перспективы развития фундаментальных наук; Т. 1 : Физика - Sharonova A. A. Anna Aleksandrovna (2018, 2018)
Заглавие с экрана